Celebrating Hazel : 1929-2013. - Sydney Children's Choir; Sydney Opera House; Sydney Symphony Orchestra ([Sydney, New South Wales] : Celebrating Hazel, 2013)
An event celebrating the life of Hazel Hawke.
Title from title screen (viewed on 27 June 2013)
Mode of access: Available online. Address as at 16/10/2013
Selected for archiving
Keywords: Hawke, Hazel, -- 1929-2013 -- Anniversaries, etc; Anniveraries; Dementia -- Australia; Prime ministers' spouses -- Australia; Australian